ETHNOPHARMACOLOGY OF PLANTS IN CHOMAN, THE KURDISTAN REGION OF IRAQ (Applied Biological Research, 2023)
Plants with therapeutic value are still the only way forward for health  care as their acceptance has grown all over the world. The information of  the utilization of traditional medicinal plants in Kurdistan region is still  at hand of the traditional herbalist. The study aimed at to identify  different medicinal plants used by traditional herbalist in Choman locale  of Erbil in Northern Iraq. Non-random probability sampling and expert  method with the aid of a in-depth interview guide were used. Only plant  species with a minimum of 0.5 relative frequency of citation were  reported. Forty-one plants exhibiting medicinal properties have been  documented. The family Asteraceae has highest abundance in the  area. Allium sativum had highest used value (0.5). Leaves (32.7%) and  fruits (23.6%) are the most utilized parts of medicinal plants in the study  area. The most prepared form of preparation is decoction (45.5%) and  direct form (30.9%). Oral is the most common application form (61.8%).  People of Choman in Kurdistan region of Iraq have long been using  medicinal plants for the treatment of various ailments like cold, cough,  fever, diabetes. It is, therefore, necessary to conduct ethnobotanical  studies in all the communities of Kurdistan region in Iraq.
Keywords: Choman; Erbil; ethnobotanical; Iraq; medicinal plants; ttraditional herbs